Curative efficiency and adverse events of alternative therapy and medicine for functional constipation in adults: A protocol for systematic review and meta-analysis. Issue 14 (8th April 2022) - Liu, Chang; Pang, Tingting; Yin, Shuang; Li, Jiahui; Yao, Junjie; Li, Hongmei; Lou, Huijuan; Lei, Siyuan; Zhang, Jiangchun; Dong, Li; Wang, Yufeng
Abstract: Background: The efficacy of alternative therapies and medications for functional constipation (FC) in adults is well established, however, the efficacy and safety of different alternative therapies and medications for FC in adults is not fully clarified. Due to there are many different alternative therapies and medications available for the treatment of febrile FC in adults, the selection of appropriate alternative therapies and medications has become an urgent issue. The purpose of this study was to evaluate the effectiveness and safety of alternative therapy and medicine for FC in adults. Methods: PubMed, Web of Science, Scopus, Cochrane Library, Embase, China National Knowledge Infrastructure, China Science and Technology Journal Database and Wanfang Data were searched to identify randomized controlled trials which focused on alternative therapy and medicine for FC in adults from December 15, 2020 to July 1, 2021. Subsequently, 2 researchers will be independently responsible for literature screening, data extraction, and assessment of their quality. This study uses The R Programming Language 4.0.2 based on Bayesian framework for NMA. Odds ratios or standardized mean differences will be modeled using Markov chain Monte Carlo methods, both with 95% confidence intervals. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusions: The conclusion of this systematic review will provide evidence for selecting an optimal alternative therapy and medicine for patients with FC in adults. Ethics and dissemination: The protocol of the systematic review does not require ethical approval because it does not involve humans. This article will be published in peer-reviewed journals and presented at relevant conferences. Systematic review registration: INPLASY202210091.